"To flip or not to flip, that's the question" - Findings from an exploratory study into factors that may influence tertiary teachers to consider a flipped classroom model - Lakshmi Chellapan; Jacques Van der Meer; Keryn Pratt; Rob Wass (Flexible Learning Association of New Zealand, 2018)
The concept of 'flipping the classroom' is relatively recent, although elements of it have been around for many years. It is generally accepted that the 'flipped classroom model' consists of replacing direct instruction, or lectures, with video-clips to be watched at home, and the use of face-to-face class time for engaging students in active learning activities. This development was brought about by the enhanced and easy access to video technologies. This model was initially adopted for use in secondary education, but is now increasingly considered by teachers in higher education. However, there is both confusion and scepticism about what this concept is, and whether there are any benefits of adopting this. In this exploratory study, the main focus was on seeking to identify what staff in three institutions of higher education in New Zealand considered to be the reasons for adopting and/or for not adopting, or challenges in adopting, this model. In this article, we will report on the findings from the survey aspect of this mixed methods study. The findings suggested that amongst the respondents there were three distinct groups, 1) those who saw no value adopting a flipped classroom model, considered there was nothing wrong with lectures, and that students would unwilling to engage in a flipped model; 2) those who considered that active learning was the main idea behind the flipped model, and that this was an old idea in a new guise; and 3) those who had or would like to implement the model, but had encountered or were anticipating some issues. The findings also suggested a range of understandings of what the 'flipped classroom' means. This highlighted the importance to clarify in any research project and reporting exactly what is meant by 'flipped classrooms' in order to avoid conceptual confusion.